N-Aryl-7-hydroxy-5-oxo-2,3-dihydro-1H,5H-pyrido-[3,2,1-ij]quinoline-6-carboxamides. The Synthesis and Effects on Urinary Output - Igor V. Ukrainets; Lyudmila V. Sidorenko; Mykola Y. Golik; Igor M. Chernenok; Lina A. Grinevich; Alexandra A. Davidenko (MDPI AG, 2018)
Continuing a targeted search for new leading structures with diuretic action among tricyclic derivatives of hydroxyquinolines, which are of interest as potential inhibitors of aldosterone synthase, the synthesis of a series of the corresponding pyrido[3,2,1-ij]quinoline-6-carboxanilides was carried out by amidation of ethyl-7-hydroxy-5-oxo-2,3-dihydro-1H,5H-pyrido[3,2,1-ij]quinoline-6-carboxylate with aniline, aminophenols and O-alkylsubstituted analogs with high yields and purity. The optimal conditions of this reaction are proposed; they make it possible to prevent partial destruction of the original heterocyclic ester and thereby avoid formation of specific impurities of 7-hydroxy-2,3-dihydro-1H,5H-pyrido[3,2,1-ij]quinolin-5-one. To confirm the structure of all substances obtained, elemental analysis, nuclear magnetic resonance (NMR) spectroscopy, and mass spectrometry were used. Moreover, the peculiarities of their 1H and 13C-NMR spectra, as well as their mass spectrometric behavior under conditions of electron impact ionization, were discussed. The effect of pyrido[3,2,1-ij]quinoline-6-carboxanilides on the urinary function of the kidneys was studied in white rats of both genders by the standard method of oral administration at a dose of 10 mg/kg. Testing was conducted in comparison with hydrochlorothiazide, as well as with structurally close pyrrolo[3,2,1-ij] quinoline-5-carboxanilides studied earlier with the same substituents in the anilide fragments. It was found that addition of one methylene unit to the heterocycle partially hydrogenated and annelated with the quinolone core has a positive impact on biological properties—most of the substances studied exhibit a statistically significant diuretic effect exceeding the activity of not only hydrochlorothiazide, in some cases, but also the action of the structural analogs. The important structural and biological regularities, which are common with pyrroloquinolines and introduced by a chemical modification, were revealed. The importance of the presence in the structure of terminal amide fragments of tricyclic quinoline-3-carboxamides of a 4-methoxy-substituted aromatic ring was particularly marked. The expediency of further study of pyridoquinolines as promising diuretic agents has been shown.